2011
DOI: 10.1093/toxsci/kfr264
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Inorganic Mercury Increases Severity and Frequency of Chronic Coxsackievirus-Induced Autoimmune Myocarditis in Mice

Abstract: Mercury is a widespread environmental contaminant with neurotoxic impacts that have been observed over a range of exposures. In addition, there is increasing evidence that inorganic mercury (iHg) and organic mercury (including methyl mercury) have a range of immunotoxic effects, including immune suppression and induction of autoimmunity. In this study, we investigated the effect of iHg on a model of autoimmune heart disease in mice induced by infection with coxsackievirus B3 (CVB3). We examined the role of tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…In contrast, type I interferon production does not appear to be involved [50]. The role of altered innate immune cell responses was also noted by Nyland et al [51], who found that prior mercury exposure caused a problematic, macrophage-driven response to viral infection in mice, leading to cardiac inflammation and an increased likelihood of autoimmunity. Mercury exposure affects the function of many organs; among these are the brain and neurological system, which are vulnerable to oxidative-induced damage [52].…”
Section: Mercurymentioning
confidence: 86%
“…In contrast, type I interferon production does not appear to be involved [50]. The role of altered innate immune cell responses was also noted by Nyland et al [51], who found that prior mercury exposure caused a problematic, macrophage-driven response to viral infection in mice, leading to cardiac inflammation and an increased likelihood of autoimmunity. Mercury exposure affects the function of many organs; among these are the brain and neurological system, which are vulnerable to oxidative-induced damage [52].…”
Section: Mercurymentioning
confidence: 86%
“…Previously, we found that in order for mercury to increase chronic myocarditis and dilated cardiomyopathy, mercury exposure had to occur prior to CVB3 infection [17]. Thus, we hypothesize that mercury modulates the early innate immune response to CVB3 infection and thereby sets in place a cascade of events ending in increased severity of myocarditis and prevalence of dilated cardiomyopathy.…”
Section: Introductionmentioning
confidence: 94%
“…In lupus-prone female BXSB mice, low dose mercury can accelerate kidney disease [15] and pretreatment with low dose mercury accelerates disease in the chronic Graft-versus-Host model of lupus in female, but not in male mice [16]. We recently reported that pretreatment with low dose mercury increases the severity of chronic autoimmune myocarditis and the prevalence of dilated cardiomyopathy in the coxsackievirus B3 (CVB3) and experimental autoimmune myocarditis models [17, 18]. However, the precise mechanisms for enhanced disease remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main contribution to human exposure is the ingestion of fish and seafood (methylmercury); however, it can also occur from dental amalgam fillings (metallic mercury), vaccines (ethylmercury) and contaminated water and air (mercury chloride) [1], [2].…”
Section: Introductionmentioning
confidence: 99%